The signaling pathways of traditional Chinese medicine in treating diabetic retinopathy - Li, Wencan; Xing, Qichang; Liu, Zheng; Liu, Renzhu; Hu, Yixiang; Yan, Qingzi; Liu, Xiang; Zhang, Jiani (Frontiers in Pharmacology, 2023)
Diabetic retinopathy (DR) is one of the common diabetic microvascular complications that occurs in the eyes and is closely associated with vision loss in working adults. However, the clinical treatment of DR is limited or accompanied by a large number of complications. Therefore, the development of new drugs for the treatment of DR is urgently needed. Traditional Chinese medicine (TCM) is widely used to treat DR in China, and its multi-pathway and multi-level characteristics can effectively address the complex pathogenesis of DR. Growing evidence suggests that inflammation, angiogenesis, and oxidative stress are the core pathological mechanisms in the development of DR. This study innovatively considers the aforementioned processes as the fundamental unit and sheds light on the molecular mechanisms and potential of TCM against DR in terms of signaling pathways. The results showed that NF-κB, MAPK/NF-κB, TLR4/NF-κB, VEGF/VEGFR2, HIF-1α/VEGF, STAT3, and Nrf2/HO-1 are the key signaling pathways for the treatment of DR by TCMs, which involved curcumolide, erianin, quercetin, blueberry anthocyanins, puerarin, arjunolic acid, ethanol extract of Scutellaria barbata D. Don, Celosia argentea L. extract, ethanol extract of Dendrobium chrysotoxum Lindl., Shengpuhuang-tang, and LuoTong formula. The purpose of this review is to update and summarize the signaling pathways of TCM in the treatment of DR and provide ideas for the development of new drugs against DR in the future.